Comparison of young Japanese underweight women with eating disorder tendencies and constitutional thinness: A cross-sectional study - Mariko Ogawa; Michiko Nakazato; Jinko Yokota; Kaori Koga (Preventive Medicine Reports)
Objective: To compare eating disorder tendencies and constitutional thinness in young underweight Japanese women and identify distinguishing factors. Methods: In September 2024, 1000 young Japanese women were recruited and categorized into three groups based on body mass index (BMI) and responses to the Sick, Control, One Stone, Fat, and Food (SCOFF) questionnaire: eating disorder tendency (BMI <18.5 kg/m2 and SCOFF-positive, n = 93), constitutional thinness (BMI <18.5 kg/m2 and SCOFF-negative, n = 219), and control (BMI 18.5–25.0 kg/m2 and SCOFF-negative, n = 435). Result: The eating disorder tendency group idealized a thinner body shape than the constitutional thinness group and reported greater dissatisfaction with their body shape; however, body dissatisfaction was highest in the control group. General health habits were similar between the constitutional thinness and control groups. Among underweight women, significant predictors of eating disorder tendency included history of anemia (odds ratio [OR]: 4.27; 95 % confidence interval [CI]: 2.13–8.56), daily physical activity (OR: 3.46; 95 % CI: 1.78–6.74), and eating before bedtime (OR: 2.44; 95 % CI: 1.16–5.15). Conclusions: General health habits differ between underweight women with and without eating disorder tendencies. A history of anemia may serve as a potential indicator for screening for eating disorders.